2018
DOI: 10.1016/j.cct.2018.07.013
|View full text |Cite
|
Sign up to set email alerts
|

An intervention to optimise the delivery of integrated tuberculosis and HIV services at primary care clinics: results of the MERGE cluster randomised trial

Abstract: A B S T R A C TObjectives: To evaluate the effect of an intervention to optimize TB/HIV integration on patient outcomes. Methods: Cluster randomised control trial at 18 primary care clinics in South Africa. The intervention was placement of a nurse (TB/HIV integration officer) to facilitate provision of integrated TB/HIV services, and a lay health worker (TB screening officer) to facilitate TB screening for 24 months. Primary outcomes were i) incidence of hospitalisation/death among individuals newly diagnosed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 26 publications
0
30
0
Order By: Relevance
“…The important losses in the cascade found might be explained by the fragmentation of TB and HIV care. Multiple studies reported that integration of TB and HIV care was an important enabler of TPT [18,38,72,74,76,79,82], while fragmentation of TB and HIV care was identified as an important barrier [34,81]. This suggests that policymakers should work to close the gap between HIV and TB care.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The important losses in the cascade found might be explained by the fragmentation of TB and HIV care. Multiple studies reported that integration of TB and HIV care was an important enabler of TPT [18,38,72,74,76,79,82], while fragmentation of TB and HIV care was identified as an important barrier [34,81]. This suggests that policymakers should work to close the gap between HIV and TB care.…”
Section: Discussionmentioning
confidence: 99%
“…Among cohorts that did not receive LTBI tests, the cumulative TPT initiation and completion were similar if PLHIV were followed at HIV clinics or other clinics (S5 Fig [18,21,24,38,51,58,66,[70][71][72][73][74][75][76]78,79,82]. The most common facilitators were related to the initial steps (identification, initial LTBI testing, and completing LTBI testing) and to initiation and completion of TPT.…”
Section: Plos Medicinementioning
confidence: 96%
See 3 more Smart Citations